2002
DOI: 10.1002/1521-3765(20020517)8:10<2397::aid-chem2397>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Heats of Hydrogenation of Compounds Featuring Main Group Elements and with the Potential for Multiply Bonding

Abstract: Reaction enthalpies are calculated for the hydrogenation reactions of main group hydrides with the potential for multiple bonding, and thus the unsaturated character of these species is determined. In addition to the global minimum structures, which leave in some cases no hope for even a single E−E bond (E=Group 13, 14, or 15 element), calculations are also performed for geometries with maximum potential for multiple bonding. The trends down the groups and the periods are established. Interpretations have to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 21 publications
1
45
0
2
Order By: Relevance
“…Computations for the reaction of the low‐valent Group 13 dimetallene HMMH (M = Al or Ga) either in the triplet state or the more stable low‐valent bridged species M(µ‐H) 2 M with H 2 to give H 2 MMH 2 showed that the heats of reaction are negative which tend to support the view that the addition of H 2 to isolable dimetallenes should also be favored 69. We found that the H 2 reacted readily ( Scheme ) at ca 25°C and 1 atmosphere pressure with dark green toluene solutions of (which dissociates at least in part to monomers in solution) to produce bleaching of the color.…”
Section: Reactions With Unsaturated Small Moleculesmentioning
confidence: 77%
See 1 more Smart Citation
“…Computations for the reaction of the low‐valent Group 13 dimetallene HMMH (M = Al or Ga) either in the triplet state or the more stable low‐valent bridged species M(µ‐H) 2 M with H 2 to give H 2 MMH 2 showed that the heats of reaction are negative which tend to support the view that the addition of H 2 to isolable dimetallenes should also be favored 69. We found that the H 2 reacted readily ( Scheme ) at ca 25°C and 1 atmosphere pressure with dark green toluene solutions of (which dissociates at least in part to monomers in solution) to produce bleaching of the color.…”
Section: Reactions With Unsaturated Small Moleculesmentioning
confidence: 77%
“…Although no reactions had been reported between any main‐group compound and hydrogen under ambient conditions, calculations by Himmel and Schnöckel69 had shown that the model species HGeGeH exhibited a highly exothermic heat of hydrogenation (Δ H θ R = ca. −250 kJ mol−1) to give H 2 GeGeH 2 which in turn displays a Δ H θ R = −150 kJ mol−1 for a reaction with further equivalent of hydrogen to give H 3 GeGeH 3 .…”
Section: Reactions With Unsaturated Small Moleculesmentioning
confidence: 99%
“…1,2 The hydrogenation reactions also differ remarkably in their thermodynamic properties from the hydrogenation of the parent diborane(4) H 2 B-BH 2 , for which hydrogenation to give two separated BH 3 molecules was calculated (with MP2) to be associated with a ∆ R H°value of not more than -4.1 kJ mol -1 . 21 The barriers for hydrogenation were also calculated for two systems. The results suggest that hydrogenation should be possible under mild conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A second approach (which is discussed further below) involves the introduction of substituents which could (and indeed do so in the examples dealt with here) cause drastic changes to the electronic properties of the element-element bond in a way that, mechanistically, H 2 activation by Ga 2 and these molecules is completely different. The research investigations were initiated with a survey employing quantum chemical calculations on a series of subvalent dinuclear main-group element hydrides of the general formula HEEH and H 2 EEH 2 (E ¼ Group 13-15 elements) and H 3 EEH 3 (E ¼ Group 14 element) [20]. In several cases, the calculated standard enthalpies for the hydrogenation of these species argue for highly exothermic processes.…”
Section: Preliminary Quantum Chemical Calculationsmentioning
confidence: 99%